Aristotle’s Trochos and Hyena - Witczak, Krzysztof Tomasz (Polskie Towarzystwo Filologiczne, 2018)
In his work On the Generation of Animals Aristotle mentions and rejects an ancient folk belief that the striped hyena (Hyaena hyaena L.) has two (male and female) sexual organs. Also he abandoned Herodorus’ false opinion on a mystical animal named trochos (Gk. τρόχος). The identification of trochos is highly doubtful. It is suggested that the Greek term may denote the Asiatic spotted hyena (Crocuta crocuta sp. asiatica), an extinct species of the hyena family, existing in prehistoric times in Europe and Asia Minor.
Keywords: Aristotle